2023
DOI: 10.3390/diagnostics13040655
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Stroma Area and Other Prognostic Factors in Pancreatic Ductal Adenocarcinoma Patients Submitted to Surgery

Abstract: Pancreatic ductal adenocarcinoma (PDAC) has a dense stroma, responsible for up to 80% of its volume. The amount of stroma can be associated with prognosis, although there are discrepancies regarding its concrete impact. The aim of this work was to study prognostic factors for PDAC patients submitted to surgery, including the prognostic impact of the tumor stroma area (TSA). A retrospective study with PDAC patients submitted for surgical resection was conducted. The TSA was calculated using QuPath-0.2.3 softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
1
1
Order By: Relevance
“…Previous studies on PBD have shown con icting results regarding the increased risk of infectious complications [14,31,[40][41][42]. In our study, we did not nd a signi cant increase in postoperative HAIs incidence associated with PBD.…”
Section: Discussioncontrasting
confidence: 60%
“…Previous studies on PBD have shown con icting results regarding the increased risk of infectious complications [14,31,[40][41][42]. In our study, we did not nd a signi cant increase in postoperative HAIs incidence associated with PBD.…”
Section: Discussioncontrasting
confidence: 60%
“…Although these biomarkers are not related to host-periphery crosstalk, once combined with TIME-TIMaE crosstalk mediating molecules, could be considered an invaluable tool for diagnostics and clinical evaluation of PC patients, already at early stages. The most frequently used and most widely validated biomarker is CA 19–9, but, due to its low specificity and high false positive and negative rate, CA 19–9 is not sufficiently reliable as a diagnostic marker in clinical practice [ 128 ]. For this reason, some studies have focused on the combined detection of CA19-9 together with other tumor markers such as carcino-embryonic antigen (CEA), carbohydrate antigen 125 (CA125), carbohydrate antigen 242 (CA242), and on novel serum biomarkers [ 129 ], microRNAs [ 130 ] or new imaging techniques such as endoscopic retrograde cholangio pancreatography and endoscopic ultrasonography [ 131 , 132 ].…”
Section: Introductionmentioning
confidence: 99%